Causal associations of hyperthyroidism with prostate cancer, colon cancer, and leukemia: a Mendelian randomization study - Xu, Feipeng; Chen, Zhenxin (Frontiers in Endocrinology, 2023)
Background: Observational studies have shown that hyperthyroidism may increase the risk of cancer, but their causal effects and direction are unclear. We conducted a two-sample Mendelian randomization (MR) study to explore the associations between genetic predisposition to hyperthyroidism and nine common types of cancer, including prostate, lung, breast, colon, leukemia, brain, skin, bladder, and esophagus cancer. Methods: We obtained summary statistics of hyperthyroidism and nine types of cancers from genome-wide association studies (GWAS). MR analysis is performed to investigate the potential causal relationship between hyperthyroidism and cancers. The inverse variance weighted (IVW) as the primary method was carried out. The robustness of the results was evaluated by sensitivity analysis. Results: Genetically predicted hyperthyroidism was associated with a declining risk of occurrence of prostate cancer (odds ratio (OR)IVW= 0.859, P= 0.0004; OR MR-Egger= 0.714, P= 0.03; OR weighted median= 0.827, P=0.0009). Additionally, there was a significant association between genetically predicted hyperthyroidism and colon cancer (OR IVW= 1.13, P= 0.011; OR MR-Egger= 1.31, P= 0.004; OR weighted median= 1.18, P= 0.0009). Hyperthyroidism was also suggestively correlated with a higher risk of leukemia based on the result of IVW and weighted median (OR IVW= 1.05, P= 0.01; OR weighted median= 1.08, P= 0.001). Results from a two-sample MR analysis suggested that hyperthyroidism was not associated with the risk of lung cancer, breast cancer, brain cancer, skin cancer, bladder cancer, and esophageal cancer. Conclusion: Our study provides evidence of a causal relationship between hyperthyroidism and the risk of prostate cancer, rectal cancer, and leukemia. Further research is needed to clarify the associations between hyperthyroidism and other cancers.